(untitled) (Journal of Atomic and Molecular Sciences, 2016)
A theoretical investigation of the non-adiabatic dynamics processes for the reaction Na(3s) + H_2 → NaH (X¹Σ^+) + H has been performed using the method of coherence switching with decay of mixing (CSDM). The integral cross sections calculated by the CSDM method are compared with the results from an adiabatic quasiclassical trajectory (QCT) calculation, which uses the same potential energy in the adiabatic representation. The product rotational polarization in non-adiabatic dynamics is presented and compared with the adiabatic results by means of the joint distributions of rotational angular momentum vectors in the scattering coordinate. It is found that the conical intersection shows significant influence on the integral cross sections of the reaction. The adiabatic effect also reduces the rotational polarization of the product NaH.